Investigation of the Effect of Environmental Education Family Involvement Activities Mother and Father’s Attitudes towards the Environment - Ahmet Erol; Hülya Gülay Ogelman (Elementary Education Online, 2023)
The aim of this study is to increase environmental attitudes of parents with 5-6 year-old children with the help of Environmental Education Family Involvement Activities. In the study, quasi-experimental design was used. Sample group of the study consisted of totally 88 parents with 5-6 year-old children, who were selected in Pamukkale district of Denizli province, by using easily accessible sampling method. There were totally four study groups in the study (two experimental groups and two control groups). The data of the study were obtained via Uzun and Sağlam (2006) by developed Environment Attitude Scale. In the analysis of the obtained data, independent samples t-test among inferential statistical techniques, OneWay Analysis of Variance for Independent Samples (ANOVA) and One-Way Analysis of Variance for Dependent Samples (ANOVA) were used. Environmental Education Family Involvement Activities were concluded to be effective significantly on total scores of environmental thoughts, behavior, and attitudes of 5-6 year old children’s mothers and fathers.